IMF Survey, Volume 35, Issue 12. (IMF Survey; IMF Survey ;, 2006)
IMF work program; de Rato in Australia, New Zealand; Improving the IEO; Swaziland, Philippines briefs; Inequality in Panama; Namibia: poverty and inequality; Gabon: post-oil era; Growth in Indian states; HIV/AIDS effect; China and India: emerging giants.